The thiol-disulfide homeostasis and its role in the pathogenesis of the experimental alimentary obesity (Bangladesh Journal of Medical Science, 2016)
Objective: According to WHO, about 30 % of people in the world are overweight that allows to characterize this disease as a new non-infection epidemic of the XXI century. More than 500 million people in the world are overweight and 250 million are obese. There is a clear tendency to increasing of alimentary obesity among people with different age, sex and nationality. The aim of the study is to investigate the thiol-disulfide homeostasis in liver tissue, adipose tissue and erythrocytes in the pathogenesis of experimental alimentary obesity.Materials and methods: 60 males, non-liner, white rats around 3 months of age with alimentary obesity were examined during the study. Experimental obesity was modeled by administering of sodium glutamate to the feed mixture in a ratio of 0.6:100.0 and adding high-calorie diet. The glutathione redox-system activity in erythrocytes, liver and adipose tissue were analyzed by the level of reduced glutathione (GSH), oxidized glutathione (GSSG), glutathione reductase (GR) and glutathione peroxidase (GP) activity.Results and Discussion: The data indicate a decrease in GSH level within 14 days of the experiment in all investigated tissues. The same trend was observed in animals on 28th day of the experiment: GSH index decreased in blood, adipose tissue and liver (P